My Beloved is Mine and I am His: A Literary Analysis of Loyalty, Responsibility, and Intimacy in Song of Songs 2:16 - Pattinaja, Aska Aprilano (Institut Agama Kristen Negeri Toraja, 2025)
The marital crises in contemporary society increasingly expose the fragility of commitment, intimacy, and mutual responsibility within husband–wife relationships. Against this backdrop, this study aims to examine Song of Songs 2:16 as a biblical text that articulates an alternative paradigm of exclusive and reciprocal marital intimacy. Employing a literary method and exegetical analysis of the Hebrew text, this research focuses on the poetic structure, key lexical expressions, and relational imagery within the verse. The analysis shows that the reciprocal phrase